Clinical features of the course of optic neuritis as a complication of idiopathic anterior uveitis (Ukrainian Journal of Ophthalmology, 2025)
Background: Uveitis is the fifth leading cause of visual impairment in developed countries and responsible for about 20% of legal blindness. A serious complication of anterior uveitis, optic neuritis, as well as the factors contributing to its development has not been investigated completely, but its early diagnosis is a challenge.Purpose: To reveal the features of the clinical course of optic neuritis as a complication of idiopathic anterior uveitis.Material and Methods: This study involved 150 patients with unilateral idiopathic anterior uveitis who were examined and treated at the Filatov Institute. Of these, 114 did not have signs of optic neuritis, and 34 had optic neuritis in the presence of uveitis. Patients underwent an eye examination including visual acuity, ophthalmoscopy, biomicroscopy, intraocular pressure (IOP) measurement, and Humphrey perimetry. Treatment involved antibiotics, non-steroidal anti-inflammatory drugs, immune suppressors, corticosteroids, and biological immune response modulators.Results: The clinical features related to inflammation were more severe in the group of patients with optic neuritis as a complication of anterior uveitis than in the group of patients with uncomplicated uveitis. Particularly, the number of keratic precipitates was high in 69.7%, hypopyon was present in 83.3%, and vitreous haze was intensive or apparent in all patients of the former group, versus no patients, one patient and 4.4% of patients, respectively, of the latter group. The number of keratic precipitates was moderately positively correlated with the development of optic neuritis in patients with anterior uveitis, (Spearman ρ, 0.566; p < 0.05). Concomitant otorhinolaryngological and odontogenic inflammatory diseases were found in 82.5% of patients with anterior uveitis. There was a significant positive association between the presence of concomitant otorhinolaryngological and odontogenic inflammatory diseases and the development of optic neuritis in patients with anterior uveitis (χ2=5.50, p=0.0191).
Keywords: idiopathic anterior uveitis; complications; optic neuritis; clinical features